PORTRAIT OF MAY 1998 RIOT IN “LUKA BEKU” - Dessy Wahyuni (Widyariset, 2013)
Literary of history is a literary work that contains elements of history. Those elements are removed through characterizations, places, and events. “Luka Beku” by Hary B. Kori’un is a short story contained those elements. Through a historical approach, this analysis presents the historicity contained in this short story. This analysis also uses mimetic approach, because this short story is a work of imaginative truth which is artificial. As a result of analysis, there is a description about a historical event in “Luka Beku”, that is May 1998 riot in Jakarta.